Inhibition of SARS-CoV-2-Induced NLRP3 Inflammasome-Mediated Lung Cell Inflammation by Triphala-Loaded Nanoparticle Targeting Spike Glycoprotein S1 - Chuda Chittasupho; Sonthaya Umsumarng; Kamonwan Srisawad; Punnida Arjsri; Rungsinee Phongpradist; Weerasak Samee; Wipawan Tingya; Chadarat Ampasavate; Pornngarm Dejkriengkraikul (MDPI AG, 2024)
The COVID-19 pandemic, caused by SARS-CoV-2, poses a significant global health threat. The spike glycoprotein S1 of the SARS-CoV-2 virus is known to induce the production of pro-inflammatory mediators, contributing to hyperinflammation in COVID-19 patients. Triphala, an ancient Ayurvedic remedy composed of dried fruits from three plant species-Emblica officinalis (Family Euphorbiaceae), Terminalia bellerica (Family Combretaceae), and Terminalia chebula (Family Combretaceae)-shows promise in addressing inflammation. However, the limited water solubility of its ethanolic extract impedes its bioavailability. In this study, we aimed to develop nanoparticles loaded with Triphala extract, termed "nanotriphala", as a drug delivery system. Additionally, we investigated the in vitro anti-inflammatory properties of nanotriphala and its major compounds, namely gallic acid, chebulagic acid, and chebulinic acid, in lung epithelial cells (A549) induced by CoV2-SP. The nanotriphala formulation was prepared using the solvent displacement method. The encapsulation efficiency of Triphala in nanotriphala was determined to be 87.96 ± 2.60% based on total phenolic content. In terms of in vitro release, nanotriphala exhibited a biphasic release profile with zero-order kinetics over 0-8 h. A549 cells were treated with nanotriphala or its active compounds and then induced with 100 ng/mL of spike S1 subunit (CoV2-SP). The results demonstrate that chebulagic acid and chebulinic acid are the active compounds in nanotriphala, which significantly reduced cytokine release (IL-6, IL-1β, and IL-18) and suppressed the expression of inflammatory genes (IL-6, IL-1β, IL-18, and NLRP3) (p < 0.05). Mechanistically, nanotriphala and its active compounds notably attenuated the expression of inflammasome machinery proteins (NLRP3, ASC, and Caspase-1) (p < 0.05). In conclusion, the nanoparticle formulation of Triphala enhances its stability and exhibits anti-inflammatory properties against CoV2-SP-induction. This was achieved by suppressing inflammatory mediators and the NLRP3 inflammasome machinery. Thus, nanotriphala holds promise as a supportive preventive anti-inflammatory therapy for COVID-19-related chronic inflammation.